Comparing Satisfaction of Undergraduate Nursing Students`: Mini-CEX vs CIM in Assessing Clinical Competence: Mini-CEX vs CIM in Assessing Clinical Competence - Saghir, Somia; Ali, Anny Ashiq; Khan, Kashif; Bibi, Uzma; Ullah, Shafaat; Ullah, Rafi; Khan, Zaifullah; Khan, Tahir (Pakistan Journal of Health Sciences, 2023)
Assessing clinical competence is crucial to medical education, ensuring that future nurses possess the necessary skills and knowledge to provide high-quality patient care. Two widely utilized assessment methods in this domain are the Clinical Integrated Map (CIM) and the Mini-Clinical Evaluation Exercise (Mini-CEX). Both approaches offer valuable insights into the clinical performance of health professionals. Objective: To assess the satisfaction level of the students between the Mini-CEX assessment versus the CIM assessment. Methods: A total of 12 BSN second-year semester-IV nursing students were enrolled in the project. The participants were randomly divided into two groups, with six students in each group. One group was assessed on the CIM tool, whereas the other group was assessed on the Mini CEX tool. The study was carried out at a private nursing college. Results: The age of the participants was between 18-25 years and most were between 18-20 years of age. Most of the participants were female and all were undergraduate’s students of semester four year two of Shifa College of Nursing. The results revealed that most students are satisfied while using Mini-CEX compared to CIM. Conclusions: Students’ abilities and interests are vital for implementing Mini-CEX successfully. It has been highlighted as a useful formative assessment tool that provides timely feedback and enhances learning outcomes.